The scientific career and contributions of Prof. Wang Yiqiu - Chen, Xuzong; Zhou, Xiaoji; Ye, Anpei; Wang, Yanhui; Chen, Jingbiao (Frontiers in Physics, 2022)
This review aims to recount the scientific career and contributions of Prof. Wang Yiqiu, as well as his contribution to the research on quantum precision measurement and cold atom physics, as a tribute to his upcoming 90th birthday. Having contributed greatly to the fields of research such as nuclear magnetic resonance, microwave atomic clocks, laser cooling of atoms, Bose-Einstein condensate, optical tweezers, and optical atomic clocks, the venerable Prof. Wang is a prominent figure in these research fields in China, and has played a pivotal role in China’s development of these subjects.